(untitled) (International Journal of Communication Systems and Network Technologies, 2020)
This work is based on the application of Linear programming tool. to find the technically high quality power supply with minimum cost. The idea is to dispatch the economical power by predicting the dispatch in such a way that the minimum generation of the cost is allowed and at the same time the allowed range of voltage is maintained along with limitations of upper and lower reactive power and current carrying capacity of the conductors is also taken care of. The entire power flow is digitally controlled with the Power World Simulation. The global power standards are maintained. The power generation is kept green as far as possible. The most important criteria is uninterrupted power supply in odd circumstances. The economy and uninterrupted power supply conditions are modelled mathematically and these equations are solved using Linear Programming. This minimizes the cost of generation of power. The PWT uses linear programming to work out the optimal power flow. The is solution is based on finding the operating point that keeps the minimum cost and still maintaining all the parameters of the power. This paper focuses on generating world class power supply at most conomical level. The very objective this work is to workout the OPF of IEEE-14 Bus System.